2017
DOI: 10.1016/j.bios.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-sensitive suspended atomically thin-layered black phosphorus mercury sensors

Abstract: The extraordinary properties of black phosphorus (BP) make it a promising candidate for next-generation transistor chemical sensors. However, BP films reported so far are supported on substrate, and substrate scattering drastically deteriorates its electrical properties. Consequentially, the potential sensing capability of intrinsic BP is highly underestimated and its sensing mechanism is masked. Additionally, the optimum sensing regime of BP remains unexplored. This article is the first demonstration of suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…Owing to the outstanding physical and chemical property of BP as a rising star, BP has been applied in many fields such as batteries anodes, selective sensors, and field‐effect transistors, and these applications have been reviewed by many articles . Apart from aforesaid applications, BP, as a promising photocatalyst, has been applied in the field of photocatalysis for solar‐to‐energy conversion, photocatalytic carbon dioxide reduction, photocatalytic hydrogenation, environmental pollutants treatment, solar‐driven nitrogen fixation and antibacterial application, and cancer treatments.…”
Section: Photocatalysis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the outstanding physical and chemical property of BP as a rising star, BP has been applied in many fields such as batteries anodes, selective sensors, and field‐effect transistors, and these applications have been reviewed by many articles . Apart from aforesaid applications, BP, as a promising photocatalyst, has been applied in the field of photocatalysis for solar‐to‐energy conversion, photocatalytic carbon dioxide reduction, photocatalytic hydrogenation, environmental pollutants treatment, solar‐driven nitrogen fixation and antibacterial application, and cancer treatments.…”
Section: Photocatalysis Applicationsmentioning
confidence: 99%
“…In the past few years, there are many articles that have reported the practical application of BP in batteries, photodetectors, sensors, field‐effect transistors, and solar cells, and these applications have been summarized in some reviews . Meanwhile, many papers have reported the application of photocatalysis field, while there is no article that has detailedly reported that BP as a photocatalyst is employed in various aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, BP has been used in flexible electronics for the development of high speed FETs (14.5 GHz) [264]-an example is shown in Figure 6b-as well as circuits [265], and ion sensors [266]. Nevertheless, although BP presents very appealing characteristics for the development of high-performance electronic devices, its fabrication for sensors has been mostly confined to mechanical exfoliation due to the impurities left by chemical exfoliation and the inability to fabricate few layer BP through CVD [267][268][269]. Recent simulations on the formation of phosphorene on catalyst surfaces by Qiu et al [270] show that phosphorene becomes unstable on the surface of most transition metals, which complicates CVD growth through the same techniques as the ones used for graphene.…”
Section: Black Phosphorusmentioning
confidence: 99%
“…So far, BP has been used as photothermal agents, photodetectors, photocatalysts, organic photovoltaics, electrocatalysts, and the storage media 19–24. BP has also been studied in the field of sensors, such as humidity sensors,25 ratiometric fluorescent probes developed by the surface modification of organic molecules,26,27 field effect transistor detection of metal ions 28. In addition, BP has a wide range of applications in the biological field, including the medicine, drug carriers, and cancer treatment 29–31.…”
Section: Introductionmentioning
confidence: 99%